Amebiasis in Mexico, 2014–2023 - Alberto Antonio-Campos; Keity J. Farfán-Pira; Alfonso D. Díaz-Fonseca; Carlos Ochoa-Velasco; Paola Hernández-Carranza; Diana M. Torres-Cifuentes (Emerging Infectious Diseases)
Amebiasis remains a public health challenge in Mexico, especially in areas with poor sanitation. Despite declining prevalence (2014–2023), hotspots persist because of socioeconomic factors such as poverty. Addressing regional disparities through targeted interventions, improved infrastructure, and education is crucial to further reduce the disease burden and prevent future outbreaks.